(untitled) (Colombia Medica, 2023)
Background: Amyloid light chain (AL) amyloidosis is characterized by amyloid fibril deposition derived from monoclonal immunoglobulin light chains, resulting in multiorgan dysfunction. Limited data exist on the clinical features of AL amyloidosis. Objective: This study aims to describe the clinical characteristics, treatments, and outcomes in Colombian patients with AL amyloidosis. Methods: A retrospective descriptive study was conducted at three high-complexity centers in Medellín, Colombia. Adults with AL amyloidosis diagnosed between 2012 and 2022 were included. Clinical, laboratory, histological, treatment, and survival data were analyzed. Results: The study included 63 patients. Renal involvement was most prevalent (66%), followed by cardiac involvement (61%). Multiorgan involvement occurred in 61% of patients. Amyloid deposition was most commonly detected in renal biopsy (40%). Bortezomib-based therapy was used in 68%, and 23.8% received high-dose chemotherapy with autologous hematopoietic stem cell transplantation (HDCT-ASCT). Hematological response was observed in 95% of patients with available data. Cardiac and renal organ responses were 15% and 14%, respectively. Median overall survival was 45.1 months (95% CI: 22.2-63.8). In multivariate analysis, cardiac involvement was significantly associated with inferior overall survival (HR 3.27; 95% CI: 1.23-8.73; p=0.018), HDCT-ASCT had a non-significant trend towards improved overall survival (HR 0.25; 95% CI: 0.06-1.09; p=0.065). Conclusions: In this study of Colombian patients with AL amyloidosis, renal involvement was more frequent than cardiac involvement. Overall survival and multiorgan involvement were consistent with data from other regions of the world. Multivariate analysis identified cardiac involvement and HDCT-AHCT as possible prognostic factors.